2021
DOI: 10.1097/ncq.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of Rationing and Quality of Nursing Care

Abstract: Background: Nursing care rationing has been a widespread problem in everyday nursing practice for many years. Purpose:The aim of this research study was to assess the prevalence of care rationing among nurses working in Poland. Methods: The study was conducted among a population of 1310 nurses. To examine the dependencies between the sociodemographics and unfinished nursing care, the Polish adaptation of the Perceived Implicit Rationing of Nursing Care questionnaire and an investigator-developed questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Although nurses reported a variety of nursing activities as not completed, the mean score showed that frequency of nursing care rationing was in the range from between 'never' and 'rarely'. The same range (less than rarely) of rationed nursing care frequency has also been found in several Polish studies (Jarosz et al, 2022;Kołtuniuk et al, 2021;Piotrowska et al, 2022;Witczak et al, 2022) or in Slovak study (Kalánková et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…Although nurses reported a variety of nursing activities as not completed, the mean score showed that frequency of nursing care rationing was in the range from between 'never' and 'rarely'. The same range (less than rarely) of rationed nursing care frequency has also been found in several Polish studies (Jarosz et al, 2022;Kołtuniuk et al, 2021;Piotrowska et al, 2022;Witczak et al, 2022) or in Slovak study (Kalánková et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…Similar results are presented in a study by Witczak et al, showing that the average level of missing nursing care amounted to 1.16 (SD = 0.7), and the predictors of rationing of nursing care were connected with the quality of patient care and overall job satisfaction-the factors to be continuously monitored since they indicate the level of rationing of nursing care [37]. The studies by Schubert et al [38] conducted on surgical, gynaecological and non-invasive treatment wards and by Młynarska et al [39] showed that nursing care is rarely rationed.…”
Section: Rationing Of Nursing Caresupporting
confidence: 86%
“…Nursing shortages may manifest themselves in this way. In addition, it may be related to care rationing, since the need to ration care—resulting, among other things, from staff shortages—affects the quality of life [ 24 , 25 ]. An interesting relationship in the values obtained for stress level and quality of life can be seen in Polish and Slovak nurses.…”
Section: Discussionmentioning
confidence: 99%